2021
DOI: 10.12659/ajcr.931992
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Hemosiderotic Synovitis of the Knee Mimicking Pigmented Villonodular Synovitis on Magnetic Resonance Imaging (MRI) in a Child: A Case Report

Abstract: Patient: Male, 13-year-old Final Diagnosis: Post traumatic hemosiderotic synovitis Symptoms: Knee pain • swelling and limitation in movements Medication: — Clinical Procedure: — Specialty: Radiology Objective: Rare disease Background: Hemosiderotic synovitis (HS) is a rare proliferative synovial disorder with incompletely understood pathophysiology. It mainly affects the knee joint. It can be confus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…One previous study in middle‐aged healthy individuals demonstrated that cartilage loss and subchondral cysts were both present in 1.5% of ankle joints, which implies that such lesions are overall uncommon 31 . Articular hemosiderin has been described in individuals without hemophilia, although rarely and to our knowledge only in case reports 32–34 . Based on these data, we hypothesize that the majority of the MRI abnormalities found in the ankles of our study population are truly signs of hemophilia‐related changes, whereas observed knee lesions may reflect normal age‐related joint degeneration to a greater extent.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…One previous study in middle‐aged healthy individuals demonstrated that cartilage loss and subchondral cysts were both present in 1.5% of ankle joints, which implies that such lesions are overall uncommon 31 . Articular hemosiderin has been described in individuals without hemophilia, although rarely and to our knowledge only in case reports 32–34 . Based on these data, we hypothesize that the majority of the MRI abnormalities found in the ankles of our study population are truly signs of hemophilia‐related changes, whereas observed knee lesions may reflect normal age‐related joint degeneration to a greater extent.…”
Section: Discussionsupporting
confidence: 59%
“…31 Articular hemosiderin has been described in individuals without hemophilia, although rarely and to our knowledge only in case reports. [32][33][34] Based on these data, we hypothesize that the majority of the MRI abnormalities found in the ankles of our study population are truly signs of hemophilia-related changes, whereas observed knee lesions may reflect normal age-related joint degeneration to a greater extent. This is in line with the low prevalence of ankle osteoarthritis and the high prevalence of knee osteoarthritis in the general population.…”
Section: Joint Status In the General Populationmentioning
confidence: 98%
“…This aligns with previous studies as well, which have shown the efficacy of MRI in the diagnosis of PVNS [ 16 , 17 ]. The MRI results of PVNS may exhibit similarities with other synovial lesions [ 18 ]. On T1-weighted images, the lesions have a signal intensity that is either low or intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…18 Therefore, MRI was a noninvasive, highly accurate diagnostic modality in characterizing PVNS and RA. 19,20 Apart from diagnosis, MRI was also useful in defining the extent of disease because the ligaments, tendons, menisci, and cartilage were visualized in addition to the lesion. 21 However, MRI has certain limitations as a routine examination method for patients.…”
Section: Discussionmentioning
confidence: 99%
“…And MRI was superior ultrasonography in the overall assessment of synovitis and erosions, proving to be the most appropriate instrument for evaluating the actual damage produced by RA 18 . Therefore, MRI was a noninvasive, highly accurate diagnostic modality in characterizing PVNS and RA 19,20 . Apart from diagnosis, MRI was also useful in defining the extent of disease because the ligaments, tendons, menisci, and cartilage were visualized in addition to the lesion 21 .…”
Section: Discussionmentioning
confidence: 99%